Currículo do Curso Técnico em Vigilância em Saúde da Secretaria Municipal da Saúde de São Paulo: integração ensino e serviço no Sistema Único de Saúde - Veltri, Marcos (2019)
This study was based on the Curriculum of technical course in health surveillance (CTHS) of Municipal health department of São Paulo Administration. The thesis consists of the proposition that the CTHS curriculum features an integrated curricular project. The research could be justified by the fact that it investigated a proposal of curricular integration in the dimensions of the teaching work, practice theory and of community teaching, which can contribute to the discussion of professional technical education policies and permanent education in health. The Professional technical education in health can contribute to the reduction of serious technical errors, in the prevention of unethical behaviors, as well as it can positively impact upon the actions and in the health programs that are already being developed in the Public Health System. The main objective of this study was to analyze the vital aspects in the relationship between the professional practice of Combating Endemic Diseases agents (students) and the proposed formation of CTHS, from 2010 to 2016, under the perspective of the course coordinators. The research investigation was set on a qualitative approach perspective. It was proposed a theoretical and practical investigation, with the assumptions of dialectical and historical materialism research method. The technical procedures were outlined by an ex post facto investigation which included as information source: bibliographical research, documentary and a field research methodology for the primary and secondary data collecting. The semi-structured script interview was the technique selected to obtain the required information to support the preparation of the response to the main objective of this study. The analysis of Bardin’s content was the method used to the organization, categorization and systematization of the human subjects’ interview content research, which was the starting point for other approaches that had as reference to socio-historical, economic and cultural policy circumstances that determined the CTHS curricular project, in its planning, deployment and execution. The results of the investigation showed that CTHS retain characteristics of an integrated curricular project in the dimensions of its ordering assumptions, in the curricular structure, in the selection of the contents, in the pedagogical strategies of teaching training and pedagogical practices developed together with the students, in particular, the opportunity for the students to experience the professional practice in real situations at work and, subsequently, the problematization of this practice. It was concluded that the vital aspects in the relationship between the professional practice of Combating Endemic Diseases agents (students) and the proposed formation of CTHS were: the working process as educational principle, the role of professional competences in the teaching process in the health area, the completeness in health as controlling training guideline for the Public Health System and the integrated curriculum as organizing pedagogical action strategy